Effectiveness of Self Blood Pressure Monitoring on Awareness and Attainment of Target Blood Pressure Goal: Nation-Wide Observational Study. (June 2015) - Jo, Sang-Ho; Seo, Jae-Bin; Kim, Sang-Hyun; Kim, Hyun-Sook; Park, Kyung-Ha; Han, Sang-Jin; Kim, Sung-Ai; Park, Woo-Jung
Abstract : Backgrounds: We investigated self blood pressure monitoring(SBPM) would improve the awareness of importance of blood pressure(BP) control, compliance of antihypertensive medications and the rate of blood pressure control in hypertensive patients. Methods: A total of 7, 751 patients who visit out-patients clinic of private and university hospitals in Korea were recommended by duty physicians to measure self BP with automatic electronic BP monitors at home. Office BP changes before and after SBPM was compared. Attainment of target BP and compliance of antihypertensive drugs were also compared before and after SBPM. Patients and duty physicians were interviewed on perception of value of SBPM. Results: Mean BP significantly decreased from 142/88 mmg to 129/80 mmHg ( P  < 0.001) and target BP attainment rate increase from 5% to 15% ( P  = 0.02). Drug compliance measured by no medication day/week increased from 0.86 day to 0.53 day ( P  = 0.013). Only 33% and 57% of patients know the normal BP range and target BP respectively in patients. Awareness of importance of BP control increased from 90% to 98% after SBPM. Ninety two percents of physicians replied SBPM is important, 94% answered SBPM is helpful in controlling BP and 90% recommended their patients to measure SBPM. Conclusions: Self blood pressure monitoring improves BP control rate, drug compliance and knowledge of patients on BP. Most physicians acknowledge the importance and SBPM and recommend it for BP control in Korea.